Evaluating the Efficacy of Topical Tacrolimus Alone and in Combination with Prednisolone for Treating Subepithelial Infiltrates in Epidemic Keratoconjunctivitis - Emine Esra Karaca; Gökhan Çelik; Şule İdacı Koç; Özlem Evren Kemer (Biomedicines, 2025)
Purpose: Epidemic keratoconjunctivitis (EKC) is a common viral ocular infection that can lead to persistent subepithelial infiltrates (SEIs), resulting in significant visual impairment and patient discomfort, necessitating effective treatment strategies beyond corticosteroid monotherapy. This study aims to evaluate the efficacy of topical tacrolimus (0.1%) ointment alone versus its combination with prednisolone (1%) drops to provide optimal therapeutic strategies for SEIs secondary to EKC. Methods: This retrospective observational study evaluates 102 eyes of ninety-five individuals. The patients were divided into two groups based on the treatment approach. The first group received tacrolimus ointment alone (n = 34), whereas the second group received a combination of prednisolone drops and tacrolimus ointment (n = 68). Best-corrected visual acuity (BCVA), the corneal subepithelial infiltrate score (CSIS), the subjective symptom score (SSS), and the Fantes corneal haze grading score (FCHGS) were evaluated before treatment and at 1, 3, 6, 9, 12, and 18 months post-treatment. Results: Both groups showed significant improvements in the BCVA, CSIS, SSS, and FCHGS values, with no significant difference between the groups at 18 months (p > 0.05). The combination therapy resulted in a significantly faster treatment response than tacrolimus alone (p < 0.05) in terms of CSIS, SSS, and FCHGS values. An increase in intraocular pressure (IOP) was observed in four patients in the combination treatment group after three months. Conclusions: Topical tacrolimus, both alone and in combination with topical prednisolone, was effective in treating subepithelial infiltrates secondary to EKC. Combination therapy may be applied early for faster recovery; however, close monitoring of IOP is necessary in individuals using topical prednisolone.